Collaborative Information Behaviour in Completely Online Groups: Exploring the Social Dimensions of Information in Virtual Environments - Hernández-Pérez, Oskar (Qualitative and Quantitative Methods in Libraries; Vol 4 No 4 (2015): December 2015 Issue, 2017)
Teamwork is encouraged nowadays as an imperative skill to better perform all critical factors, including information, that are involved in the project-based structures of many organizations. Due to the inherently collaborative nature of group activities, when groups search, retrieve, manage and disseminate information, new relationships with information emerge which result in collaborative informational behaviours. The aim of this research was to study a specific case of collaborative information behaviour in completely online groups, which initiated, developed and completed a teamwork project in the virtual learning environment of the Open University of Catalonia‟s Virtual Campus. The study methodologically developed a multidimensional analytical approach, built from a set of twelve interrelated variables in three dimensions. A field study was conducted using virtual ethnographic techniques. Findings reveal that the collaborative information behaviour in completely online groups seems to be particularly influenced by the factors related to the internal group dynamics (e.g. leadership style, degree of cohesion, or group rules).